The Problem with Capital Punishment and Why It Should Be Abolished in America - Jones, Vincent R. (Lexington Books, 2023)
One of the most controversial subjects in criminal law is whether or not we should continue to use capital punishment as the ultimate punitive sanction. The intended focus of The Problem with Capital Punishment and Why It Should Be Abolished in America is to take a harsh, critical look at theories in support of the use of this form of punishment and expose the truth about capital punishment: it is extremely costly; it is arbitrarily applied; there have been too many innocent persons exonerated from death row; and the only consistency with execution seems to be that of the mentally ill, the poor, and those without adequate legal representation and by using methods that are inhumane and “cruel and unusual”. This book shows that our current system of capital punishment is fraught with error, insanely expensive, and administered in such a manner that the possibility of executing a completely innocent person is not only possible but likely if we continue upon our present course. After reading this book, the reader will be left with no reasonable doubt that the time has come to abolish capital punishment in America.